Whether Company Size and Working Capital Turnover are Related to Current Ratio - Seftiani, Lisa; Sulbahri, Rifani Akbar; Aryani, Dwi Septa (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to determine the effect of company size and working capital turnover ratio on liquidity in insurance companies listed on the Indonesia Stock Exchange in 2019-2022. The method used in this research is quantitative method and associative research type. The sample of this research is insurance companies listed on the Indonesia Stock Exchange in 2019-2022, totaling 15 companies with sampling techniques using purposive sampling method. Simultaneously, the results of this study indicate that company size and working capital turnover ratio simultaneously affect liquidity in insurance companies listed on the Indonesia Stock Exchange in 2019-2022 this is because the sig F value is 0.000 <0.05. Partially, the results of this study indicate that company size partially affects liquidity in insurance companies listed on the Indonesia Stock Exchange in 2019-2022, this is because the sig t value of the company size variable is 0.002 <0.05. Working capital turnover ratio partially affects liquidity in insurance companies listed on the Indonesia Stock Exchange in 2019-2022, this is because the sig t value of the working capital turnover ratio variable is 0.021 <0.05.